2023
DOI: 10.3390/jcs7070290
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Processing of Polymer/Nanocarbon Nanocomposite Nanofibers—Design, Features, and Technical Compliances

Abstract: Polymeric nanofibers have emerged as exclusive one-dimensional nanomaterials. Various polymeric nanofibers and nanocomposite nanofibers have been processed using the thermoplastic, conducting, and thermoset matrices. This review aims to highlight the worth of electrospinning technology for the processing of polymer/nanocarbon nanocomposite nanofibers. In this regard, the design, morphology, physical properties, and applications of the nanofibers were explored. The electrospun polymer/nanocarbon nanofibers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…Electrospinning is broadly applied for nanofiber fabrication with unique and advanced properties [1,2]. It was first reported in 1914 by Zeleny [3], but the US patented it by Formhals in 1934 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is broadly applied for nanofiber fabrication with unique and advanced properties [1,2]. It was first reported in 1914 by Zeleny [3], but the US patented it by Formhals in 1934 [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a surge of interest in composites containing conductive polymers [5][6][7][8][9] for application in supercapacitors. It has been reported that the capacitance of PPy composites containing ferromagnetic lanthanum strontium manganate nanoparticles is higher than the capacitance of pure PPy electrodes [10].…”
Section: Introductionmentioning
confidence: 99%